Analisis Dampak Keberadaan Website Desa terhadap Transparansi dan Partisipasi Masyarakat Desa Tuk - Kodriyah, Dewi; Vidiati, Cory (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research is motivated by the urgency of implementing Good Governance principles at the village level through digital innovation in the form of a village website that serves as an instrument of transparency and public participation. The purpose of this study is to analyze the impact of the Tuk Village website on increasing public information transparency and community participation in village governance. This study uses a qualitative method with a descriptive approach, through field observations, document studies, and interviews with village officials and the community. The results show that the Tuk Village website has contributed significantly to opening access to public information, such as the publication of the Village Budget (APBDes), Village Work Plan (RKPDes), and online financial reports. However, the effectiveness of digital transparency is still limited due to internal constraints such as low human resource capacity in content management and external constraints such as low digital literacy and community participation. The findings indicate that digital transparency has not yet fully translated into substantive accountability, but rather remains administrative in nature. The implications of this research emphasize the need to strengthen the capacity of village officials, improve community digital literacy, and integrate technology, participation, and accountability so that village websites can function not only as information media but also as a means of participatory democracy that strengthens public trust and the effectiveness of village governance.